Quem são eles? : os bastidores da política e a diversidade de papéis dos Chefes de Gabinete - Cardoso, Suliane da Silva (2019)
There are distinct types of professional charges/positions that act between the political spheres. The legislative power, considered the closest channel between representatives and represented, it counts with the work of elected city councilmen and its parliamentarian staffs to enable policies that impact life in society. The present study has as an object of analysis the charge of Chief of Staff, which is part of the advisors team under the prior responsibility to help the parliamentary in all that is requested, causing them to be involved with the practices and political actions developed in the institutional spaces. Permeating aspects that range from its political socialization, passing thru its professional practices, to its recruiting process, it is intended, therefore, to answer which are the entering processes of chiefs of staffs in the political world and which activities are practiced by them, in order to comprehend this employees characteristic, specifically about the municipal legislative ambit. Therefore/ for this purpose, it will be used two research methods of qualitative approach: the ethnography and the biographic narrative. The tools used were specially open and semi-structured interviews, field observations and documents analysis. As results of the research, there have been identified specific profiles of activities developed by the chiefs of office, as well as indicators about their political involvements that allow more information about how the recruiting processes occur.